Tensile strength and refractive index of polyacrylonitrile-methylacrylate (PAN-MA) Copolymer films - Gogulamurali, N.; Ramaswamy, D. (1987)
The tensile strength and refractive index of polyacrylonitrile-methylacrylate (PAN-MA) in the ratio of 94% 6% (System 1) and 97% 3%(System II) are investigated and the contribution of methyllacrylate (MA) content to the stiffness and clarity of the copolymer film, (PAN-MA) is interpreted. From the values obtained, the increase in MA content decreases the stiffness and clarity of the film.The morphological studies of the control and fractured surfaces also reveal that higher MA content in the Copolymer PAN-MA decreases the fibrillar nature and in turn the work done to fracture. Therefore System II appears to be more compatible with that of leather as surface coating material than System I.